2019
DOI: 10.2298/ntrp190705002r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MOX fuel and the ENDF/B-VIII on the AP1000 neutronic parameters calculations by using MCNP6

Abstract: 1 Phys ics De part ment, Fac ulty of Sci ence, Zagazig Uni ver sity, Zagazig, Egypt 2 Phys ics De part ment, Col lege of Sci ence, Jouf Uni ver sity, Sakaka, Saudi Ara bia 3 Zagazig Higher In sti tute for En gi neer ing and Tech nol ogy, Zagazig, Egypt 4 Nu clear and Ra dio log i cal Reg u la tory Au thor ity, Cairo, Egypt Sci en tific pa per https://doi.org/10.2298/NTRP190705002RThe pres ent work stud ies the ef fect of in tro duc ing MOX fuel on West ing house AP1000 neutronic pa ram e ters. The neutronic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…NODAL3 code requires cross-section data for fuels and other materials in the reactor core. The crosssection data play a very important role in obtaining accurate neutronic calculation results [5,6]. To un-derstand the effect of using different cross-section data on neutronic parameters, the PWR MOX/UO 2 Core Transient Benchmark case was chosen to be evaluated [7].…”
Section: Introductionmentioning
confidence: 99%
“…NODAL3 code requires cross-section data for fuels and other materials in the reactor core. The crosssection data play a very important role in obtaining accurate neutronic calculation results [5,6]. To un-derstand the effect of using different cross-section data on neutronic parameters, the PWR MOX/UO 2 Core Transient Benchmark case was chosen to be evaluated [7].…”
Section: Introductionmentioning
confidence: 99%
“…These identified issues, therefore, reduced the feasibility of using 100% conventional MOX fuel in place of UO 2 fuel cycle in a reactor core. However, studies by Reda, Gomaa, Bashter, Amin 17 and Fetterman 18 have demonstrated the feasibility of replacing a certain percentage of AP1000 reactor core fuel with the conventional MOX, which showed relative good neutronic properties. But the core experienced reduction on the moderator and fuel temperature coefficients of reactivity being important safety parameters, in which the extent of reduction depends on the number of fuel rod/assembly replaced.…”
Section: Introductionmentioning
confidence: 99%
“…But the core experienced reduction on the moderator and fuel temperature coefficients of reactivity being important safety parameters, in which the extent of reduction depends on the number of fuel rod/assembly replaced. Moreover, the replacement of UO 2 fuel rods/assemblies with the conventional MOX fuel still produced large‐scale high‐level radioactive isotopes, retaining strong proliferation risk and waste challenges 17,19 . These issues associated with the conventional MOX were found to be addressed by the thorium mixed oxide fuel 19 …”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of recycling plutonium to make a MOX fuels are reducing the amount of enriched uranium and reducing radioactive waste generated from spent nuclear fuel [1]. For this reason, research is still being carried out regarding the use of MOX fuel in PWR reactors [2][3] [4]. Most light water-cooled (LWR) reactors have been licensed to use MOX fuels at fraction up to 30% or more on the reactor core [5] [6].…”
Section: Introduction *mentioning
confidence: 99%